2006
DOI: 10.1002/bit.21148
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of phenol by aerobic granules and isolated yeast Candida tropicalis

Abstract: Aerobic granules effectively degrade phenol at high concentrations. This work cultivated aerobic granules that can degrade phenol at a constant rate of 49 mg-phenol/g x VSS/h up to 1,000 mg/L of phenol. Fluorescent staining and confocal laser scanning microscopy (CLSM) tests demonstrated that an active biomass was accumulated at the granule outer layer. A strain with maximum ability to degrade phenol and a high tolerance to phenol toxicity isolated from the granules was identified as Candida tropicalis via 18S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(68 citation statements)
references
References 41 publications
3
61
1
Order By: Relevance
“…Aerobic granules of C. tropicalis were sufficient enough to degrade the phenol up to 1000 mg/l. The highest concentration of phenol (>1000 mg/l) was inhibitory for C. tropicalis present in the aerobic granule (Adav et al, 2007). Vilimkova et al (2008) found NADPHdependent phenol hydroxylase and catechol-1, 2-dioxygenase from C. tropicalis which helps in the degradation of phenol.…”
Section: Biodegradation Of Phenol By Free and Immobilized Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…Aerobic granules of C. tropicalis were sufficient enough to degrade the phenol up to 1000 mg/l. The highest concentration of phenol (>1000 mg/l) was inhibitory for C. tropicalis present in the aerobic granule (Adav et al, 2007). Vilimkova et al (2008) found NADPHdependent phenol hydroxylase and catechol-1, 2-dioxygenase from C. tropicalis which helps in the degradation of phenol.…”
Section: Biodegradation Of Phenol By Free and Immobilized Cellsmentioning
confidence: 98%
“…By comparing the previous isolates for phenol degradation, it was observed that the current strain is a more efficient and degraded higher concentration of phenol. Among the various species of yeast, C. tropicalis is the most studied yeast species for its potential for phenol degradation (Yan et al, 2005;Adav et al, 2007;Zhou et al, 2011;Ahmad et al, 2013;Basak et al, 2014a;Long et al, 2014). Besides C. tropicalis, other yeast such as C. lipolytica, Candida utilis, Candida albicans, Trichosporon montevideense, and Trichosporon cutaneum were also used to degrade the phenol and its derivatives (Chen et al, 2002;Vilimkova et al, 2008;Liu et al, 2011;Gerginovaa et al, 2014).…”
Section: Biodegradation Of Phenol By Free and Immobilized Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a novel biotechnique, characterized by self-immobilization of microorganisms through cell-to-cell adhesion, without any carrier material. Aerobic granules are reported for a very high cell concentration (up to 15,000 mg/l) and to be able to decontaminate high-strength wastewater (up to 15 kg COD/m 3 /day) [51]. However, this technology is still in a development stage.…”
Section: Immobilization Techniquesmentioning
confidence: 99%
“…Yeasts show the ability to oxidize and cleave aromatic rings where phenol, being a reduced carbon source, can serve as an energy rich nutrient [7][8][9]. In this regard several process strategies have been proposed [5].…”
Section: Introductionmentioning
confidence: 99%